STRATEGI OPTIMALISASI PENGAWASAN BARANG BAWAAN PENUMPANG: STUDI KASUS PADA KPU BC SOEKARNO-HATTA - Muhammad, Fadhal (Unit Penerbitan Politeknik Keuangan Negara STAN, 2024)
The Directorate General of Customs and Excise (DGCE) undertakes a unique dual role of supervision and facilitation. In supervising passenger goods, the KPU BC Soekarno-Hatta, as the DGCE institution overseeing Indonesia's largest international airport, applies risk management to maximize both functions simultaneously. However, over the past two years, the performance of KPU BC Soekarno-Hatta has received various complaints from the public. Thus, this study aims to analyze the baggage supervision mechanisms implemented by customs officers at KPU BC Soekarno-Hatta and identify strategies to optimize passenger goods supervision to enhance compliance and user satisfaction. A qualitative research method is used to elucidate this phenomenon. A series of interviews with goods examiners at KPU BC Soekarno-Hatta was conducted, followed by content analysis of the interview and documentation results. The analysis revealed that the implementation of risk management in passenger goods supervision at KPU BC Soekarno-Hatta faces several challenges, including the need to enhance the quality of examiner decisions and the low hit rate in supervision efforts. Therefore, KPU BC Soekarno-Hatta needs to optimize passenger profiling and more effectively disseminate information among examiners.